2022
DOI: 10.3390/app122412980
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning-Based Correction Method for High-Frequency Surface Wave Radar Current Measurements

Abstract: An algorithm based on a long short-term memory (LSTM) network is proposed to reduce errors from high-frequency surface wave radar current measurements. In traditional inversion algorithms, the radar velocities are derived from electromagnetic echo signals, with no constraints imposed by physical oceanographic processes. In this study, sea surface winds and tides are included in the LSTM algorithm to improve radar data. These physical factors provide the LSTM network with more oceanic information by which to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Figure 9 provides comparisons of the ADCP and radar EOF ellipses for the total velocities and residual currents. The EOF ellipse method was described in our previous work [38,46]. In Figure 9a, the ADCP ellipses at points R1 and R6 closely resemble the radar ellipses, both in size and phase.…”
Section: Total Velocitymentioning
confidence: 74%
See 1 more Smart Citation
“…Figure 9 provides comparisons of the ADCP and radar EOF ellipses for the total velocities and residual currents. The EOF ellipse method was described in our previous work [38,46]. In Figure 9a, the ADCP ellipses at points R1 and R6 closely resemble the radar ellipses, both in size and phase.…”
Section: Total Velocitymentioning
confidence: 74%
“…γ = 0.96, α = 5.8 • also demonstrate the consistency between the two vector sequences. In addition, the rotary power spectral analysis method [46] is used to compare the vector velocities of HF radar and ADCP. Similar to the radial velocity spectrum, the observed radar and ADCP data exhibit strong consistency.…”
Section: Total Velocitymentioning
confidence: 99%
“…In the prediction process, respective parameters were used to validate the correction effect on radar data. Prev experiments conducted by Zhu et al [31,32] have shown that the model's correctio radar data is a function of time. Therefore, this study also conducted sensitivity ex ments on the time of the input data in order to obtain the optimal tow route and tow time for correcting radar data.…”
Section: Empirical Orthogonal Function (Eof) Ellipsementioning
confidence: 99%
“…We are dedicated to enhancing the quality of full-field radar data through machine learning methods to obtain a high-quality HF radar dataset. Yang et al [33] demonstrated the feasibility of a single-point correction using machine learning. However, due to limited in-situ data and the high costs of deploying and maintaining mooring ADCPs, it is imperative to develop a neural network-based method for cruising ADCP measurements.…”
Section: High-frequency Radarmentioning
confidence: 99%